Language Acquisition and L2 Language: A Literature Review - Putra, Ilham Attamimi Scenda (Majapahit Journal of English Studies, 2025)
Language acquisition, particularly second language (L2) learning, has been a central focus of linguistic and educational research. This literature review synthesizes recent studies (2020–2024) to explore key theories, factors, and methodologies in L2 acquisition. The review highlights the role of cognitive, social, and technological factors in shaping L2 learning outcomes. Findings suggest that while individual differences such as age, motivation, and aptitude remain critical, emerging technologies and innovative pedagogical approaches are increasingly influential. This article concludes with implications for future research and practice in L2 teaching and learning.